Selective Small Molecule Targeting β-Catenin Function Discovered by In Vivo Chemical Genetic Screen - Jijun Hao; Ada Ao; Li Zhou; Clare K. Murphy; Audrey Y. Frist; Jessica Keel; Curtis A. Thorne; Kwang‐Ho Kim; Ethan Lee; Charles C. Hong (2013)
The canonical Wnt signaling pathway, mediated by the transcription factor β-catenin, plays critical roles in embryonic development and represents an important therapeutic target. In a zebrafish-based in vivo screen for small molecules that specifically perturb embryonic dorsoventral patterning, we discovered a compound named windorphen that selectively blocks the Wnt signal required for ventral development. Windorphen exhibits remarkable specificity toward β-catenin-1 function, indicating that the two β-catenin isoforms found in zebrafish are not functionally redundant. We show that windorphen is a selective inhibitor of p300 histone acetyltransferase, a coactivator that associates with β-catenin. Finally, windorphen robustly and selectively kills cancer cells that harbor Wnt-activating mutations, supporting the therapeutic potential of this Wnt inhibitor class.